Two new species of the genus Rhadinoloricaria from Venezuela, and comments on the taxonomic status of species included in Rhadinoloricaria (sensu lato) (Siluriformes: Loricariinae) - Provenzano-Rizzi, Francisco (Zootaxa, 2026)
Two new species belonging to the genus Rhadinoloricaria were found in the fish collection of the Museo de Biología de la Universidad Central de Venezuela (MBUCV-V). The two new species inhabit localities at the Orinoco River basin in Venezuela, one species come from the Cuchivero and Caura Rivers, Bolívar state, and the second species from the upper Orinoco, Casiquiare, Mavaca and Manapiare Rivers, Amazonas state. These localities extend considerably the northern boundary of the geographic distribution of the genus. The two new species exhibit the external morphology and buccal ornamentation pattern similar to those observed in the three species included in Rhadinoloricaria (sensu stricto). They can be distinguished from congeners and from each other by: snout shape, pattern of plates covering the abdomen, head and body coloration pattern, morphology of the first and second predorsal plates, and some morphometric values. Some specimens belonging to the new species of Rhadinoloricaria from the Amazonas state plus specimens of Apistoloricaria laani and A. ommation were used in molecular analyses performed previously. These and additional specimens plus the holotype of A. listrorhinos, deposited at the fish collections of the Academy of Natural Sciences Philadelphia, Drexel University (ANSP) and the Auburn University Museum of Natural History (AUM) were available to this study. These facts led to a re-evaluation of all species included in Apistoloricaria and their comparison with the species included in Rhadinoloricaria (sensu lato). In this article the two new species of Rhadinoloricaria from Venezuela are described. The comparative analyses performed support that Apistoloricaria, except A. listrorhinos, and Rhadinoloricaria are distinct and valid genera. Also, the analysis suggest that new molecular and morphological analyses are needed to elucidate the appropriate taxonomic status for all species included in Rhadinoloricaria (sensu lato) and to proposes new hypothesis of phylogenetic relationships between species within the Pseudohemiodon group.